Being mindful, easing suffering : reflections on palliative care - Johns, Christopher (J. Kingsley Publishers, 2004)
Annotation "Written by an experienced palliative care nurse, trainer, and complementary therapist, Being Mindful, Easing Suffering is an essential resource for professionals working with the seriously ill and the dying. Chris Johns describes how he has combined traditional medical, and more reflective models in his palliative practice, enabling him to work mindfully to alleviate physical and non-physical pain and suffering throughout the health-illness cycle. With reference to ideas from Buddhist philosophy around compassion and reflective knowing, this important book shows how the core task of those working in palliative care is to nurture the spiritual growth and development of their patients and, in turn, themselves."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.